BRIDGING DIVIDES: THE SOCIOLINGUISTIC DYNAMICS AND CULTURAL SIGNIFICANCE OF CREOLE LANGUAGE EMERGENCE - Tog‘ayev , Sarvar (Scientific practical conference, 2025)
Creole languages represent a fascinating intersection of linguistics, history and social dynamics, showing how linguistic contact between various linguistic communities can give birth to entirely new linguistic forms. Defined as stable and entirely developed languages which emerge from the process of pidginization - where speakers of different mother tongues meet for communication purposes - the languages of runners generally develop in contexts of socio -economic and cultural interaction, often in conditions of linguistic domination and socio -political hierarchies (Thomason and Kaufman, 2023). These languages generally mix elements from several parental languages, with phonological and syntactic simplifications, as well as the lexical contributions of interaction linguistic communities. Creoles arise when these pidgin languages undergo a nativision, adopted by children as a first language in a community framework, which stabilizes and further widens their grammatical and lexical resources.